Analgesic and anti-inflammatory effects of feeding aqueous date palm fruit (Pheonix dactylifera L.) extract on injury in rats - Umar, Maryam Ibrahim
The Pharmacological drugs Non steroid anti-inflammatory drugs (NSAIDS) and narcotics that are available in the management of pain and inflammation comes with a serious adverse effect as revealed in a study. Thus this study aims to evaluate the analgesic and anti-inflammatory effects of feeding date palm fruit aqueous extract on injury. The study was an experimental research carried out at Universiti Sultan Zainal Abidin, Kuala Terengganu, Malaysia. Twenty four Sprague Dawley rats were used in this research, four groups of rats were randomly assigned with six rats per group based on law of diminishing returns. The group received different interventions of 500 mg of aqueous extract of date palm, 300 mg of aqueous extract of date palm; Paracetamol and normal saline, hot tail flick test was used to evaluate the analgesic activity of the rats, while 5% croton-oil solution in acetone was used to assess the anti-inflammatory activity in each group. Statistical Package of Social Science (SPSS) software version 20 was used to perform the analysis. Non-parametric analysis was used; Kruskal Wallis H test was used followed by pair wise comparison test. Data gathered were analysed using the descriptive and inferential statistics. Result showed that the statistical significant median difference of the analgesic and anti-inflammatory effect of date fruit aqueous extract (DFAE) was revealed at (p= 0.001, x2 = 17.84) and (p= 0.002, x2 = 14.80) respectively. In addition, the significant difference of the analgesic effect of DFAE lies between normal saline and 500 mg DFAE (p= 0.001, x2 = -15.250). Likewise the significant difference of the anti-inflammatory effect of DFAE lies between group that received paracetamol, and 300 mg DFAE (p= 0.027, x2 = 0.027), paracetamol and normal saline (p= 0.001, x2 = 15.717), and 500 mg DFAE and normal saline (p= 0.031, x2 = 11.467). This research can provide the understanding of the analgesic and anti-inflammatory response of feeding date palm fruit extract on injury in rats.